Deploiment of the national research and educational network “URAN” in the frame of the state program “information and connunication technology in education and science” for 2006-2010 (Journal of Information Technologies in Education (ITE), 2009)
It is shown results of connection of universities and scientific institutions to URAN network including optic fibers deployment in Ukrainian cities and URAN-GEANT 10 Gbps. It is discussed also means of providing of uninterruptable service to metropolitan area network users and implementation of network applied services.
Keywords: fiber optic lines; GEANT; Internet; telecommunication; URAN network